FORTIFICATION OF CATFISH (Pangasiushypopthalmus) BONE MEAL ON BAKED BROWNIES FOR CONSUMER ACCEPTANCE - Wibowo Pardosi; Desmelati Desmelati; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This research was aimed to determine the effect of fortification ofcatfish (Pangasiushypopthalmus) bone mealon baked browniesfor consumer acceptance with different concentrations. The research was conducted in two stages: 1) the production of catfish bone meal, 2) the production of baked brownies with addition of catfish bone meal. The method used in this research was an experimental method, using a Completely Randomized Design (CRD) non factorial. The results showed that the baked brownies which fortified 20 g ofcatfish bone meal (K3) was the best treatment based on aroma (7.45), moisture content (32.34%), protein content (4.73%),and calcium content (0.54%).Meanwhile for taste and appearance that the baked brownies which fortified 10 g catfish bone meal (K1) was most preferred with value of taste 7.24 and appearance 7.15, for texture and ash content that the baked brownies which fortified 15 g (K2)catfish bone meal was the best treatment with value 6.80 and 4.43%, respectively. Keywords: Consumer acceptance, baked brownies, catfish bone meal, Pangasiushypopthalmus